Improved antibacterial efficiency of inhaled thiamphenicol dry powders: Mathematical modelling of in vitro dissolution kinetic and in vitro antibacterial efficacy - Wang, J.; Grégoire, N.; Marchand, S.; Kutter, J.P.; Mu, H.; Moodley, Arshnee; Couet, W.; Yang, M. (Elsevier, 2020)
Thiamphenicol (TAP) is reported to be effective against many respiratory pathogens including methicillin-resistant Staphylococcus aureus (MRSA). However, its poor solubility in water remains as one of the obstacles hindering the preparation of inhalable TAP formulations. The aim of this study was to improve the dissolution rate of TAP by micronization, and investigate whether variations in the dissolution rates of TAP would affect its in vitro antibacterial activity. Inhalable dry powders composed of TAP microcrystals (MDP) or nanocrystals (NDP) were prepared by using a wet ball milling method followed by spray drying. The morphology, solid state and in vitro dissolution of these dry powders were characterized. In vitro antibacterial activities of the inhalable TAP dry powders against a MRSA strain were evaluated. A dissolution-efficacy model relating antibacterial activity with time and dissolution rate was established via modified time-kill assays. Upon being spray dried, the volumetric mean diameters of MDP and NDP were found to be around 5 µm. Solid state analyses showed that MDP and NDP possess the same crystalline form as the raw materials. NDP exhibited faster in vitro dissolution rate as compared to MDP. The in vitro antibacterial efficiency of NDP and MDP were superior to raw TAP when the test was performed at a TAP concentration of 32 mg/L. Simulated colony forming units predictions were consistent with the result measured in the time-kill experiments with Raw TAP, MDP and NDP. This study characterized the effect of the dissolution rate of TAP dry powders on in vitro antibacterial activity against MRSA, and an enhanced antibacterial activity of TAP was observed with an increase in the dissolution rate of TAP from the dry powders at certain concentration ranges.